2000
DOI: 10.1001/archsurg.135.6.627
|View full text |Cite
|
Sign up to set email alerts
|

Healing of Diabetic Foot Ulcers and Pressure Ulcers With Human Skin Equivalent

Abstract: In patients with diabetic foot and pressure ulcers, early intervention with biological therapy will either halt progression or result in rapid healing of these chronic wounds. Design: In a prospective nonrandomized case series, 23 consecutive patients were treated with human skin equivalent (HSE) after excisional debridement of their wounds. Setting: A single university teaching hospital and tertiary care center. Patients and Methods: Twenty-three consecutive patients with a total of 41 wounds (1.0-7.5 cm in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
96
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 159 publications
(98 citation statements)
references
References 43 publications
1
96
0
1
Order By: Relevance
“…These FDA-approved treatments are clinically efficacious and include PDGF-BB (23), fibroblasts delivered in an absorbable mesh (24), and fibroblasts and keratinocytes delivered in type 1 collagen (25). If simultaneously combined with current therapies, potential treatments targeting eNOS activation and EPC recruitment might further stimulate healing.…”
Section: From Bench To Bedsidementioning
confidence: 99%
“…These FDA-approved treatments are clinically efficacious and include PDGF-BB (23), fibroblasts delivered in an absorbable mesh (24), and fibroblasts and keratinocytes delivered in type 1 collagen (25). If simultaneously combined with current therapies, potential treatments targeting eNOS activation and EPC recruitment might further stimulate healing.…”
Section: From Bench To Bedsidementioning
confidence: 99%
“…27 . Purified growth factors 28 and cultured human cells [29][30][31] have both been approved by the Food and Drug Administration to accelerate closure of non-healing wounds. This has transformed the field of wound healing by establishing the efficacy of a topical growth factor and cell therapy.…”
Section: Introductionmentioning
confidence: 99%
“…We compared our results with two RCTs [4,11]. An RCT with BBSS treatment for diabetic foot ulcers (DFU) on 208 patients with non-ischemic, chronic plantar diabetic foot ulcers done by Veves et al, showed that, at 12 weeks, 56% of the BBSS treated patients achieved complete wound healing in comparison with 38% of the control group, with the median time to complete closure being 65 days for the BBSS treated group and 90 days in the control group.…”
Section: Discussionmentioning
confidence: 99%